2017
DOI: 10.4103/ijpc.ijpc_82_17
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among cancer patients

Abstract: Introduction:Cancer is a leading cause of death. People living with cancer experience a variety of symptoms. Quality of life (QOL) is a major concern of patients with terminal cancer. Symptoms affect their QOL. Management of symptoms improves distress and QOL.Objective:The objective of the study was to assess the QOL among cancer patients.Materials and Methods:A survey was conducted among 768 cancer patients selected by a convenient sampling technique. Data was collected from cancer patients by interview techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
155
4
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(185 citation statements)
references
References 21 publications
16
155
4
10
Order By: Relevance
“…A study by Nayak MG et al, including a number of participants very similar to the number of subjects in our own research, showed that the mental well-being of the respondents influenced feelings of significant depression among 54.4% of participants and that the majority (98.3%) did not feel comfortable taking part in social life. Most of the patients feared disease recurrence (76.2%) and disability (62.1%) [ 26 ]. A comprehensive study of a US oncology centre involving nearly 4500 patients aged 19 years and older showed high rates of psychological symptoms that met the criteria for clinical diagnoses such as depression, adaptive disorders and anxiety, which was confirmed by subsequent studies by other scientists [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Nayak MG et al, including a number of participants very similar to the number of subjects in our own research, showed that the mental well-being of the respondents influenced feelings of significant depression among 54.4% of participants and that the majority (98.3%) did not feel comfortable taking part in social life. Most of the patients feared disease recurrence (76.2%) and disability (62.1%) [ 26 ]. A comprehensive study of a US oncology centre involving nearly 4500 patients aged 19 years and older showed high rates of psychological symptoms that met the criteria for clinical diagnoses such as depression, adaptive disorders and anxiety, which was confirmed by subsequent studies by other scientists [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that quality of life in cancer patients was low. (Nayak et al, 2017;Driessen et al, 2012). Low quality of life will be displayed by a decrease in physical conditions, poor social/family relationships, unstable mood conditions, and functional conditions in living everyday life and at work becomes low.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, during chemotherapy treatment, patients often develop disease-related and chemotherapy-related symptoms, such as pain, nausea, depression, and gastrointestinal complications, among others, which affect overall well-being and quality of life. 18 Many of these treatment-related symptoms are managed with medications commonly referred to as "supportive care medications, " such as clopidogrel, omeprazole, ondansetron, voriconazole, warfarin, and others. Most supportive care regimens for patients undergoing chemotherapy include multiple drugs with well-characterized drug-gene prescribing guidance.…”
Section: Rationale For Preemptive Panel-based Testingmentioning
confidence: 99%